The Impact of Strategic Leadership on Competitive Advantage: The Mediating Role of Ambidexterity and Information System: Evidence from Islamic Banks in Jordan - Amena Sibghatullah; Muhammad Raza (International Journal of Informatics and Information Systems, 2020)
The purpose linked with the existing study is to examine the impact of strategic leadership on the competitive advantage of the Islamic banks in Jordan. The mediating analysis of organizational ambidexterity and information system among the links of strategic leadership on the competitive advantage of the Islamic banks in Jordan also included in the aim of the ongoing study. This study has executed the quantitative techniques of data collection through which data has been gathered from the employees of the Islamic banks by using questionnaires. The analysis part of the existing study has been accomplished by using the AMOS. The results indicated that the positive nexus has been found among the links of strategic leadership and competitive advantage while the findings also exposed that the ambidexterity positive mediates among the links of strategic leadership and competitive advantage of the Islamic banks in Jordan. These findings provided the guidelines to the regulators while formulating regulation for competitive advantage along with leadership and also helpful for the future studies who aim to investigate this area in the future.